Investigating Viewer Engagement Dynamics Through Toxicity and Social Network Analysis in the Muara Enggelam Documentary Video - Singgalen, Yerik Afrianto (International Journal on Social Science, Economics and Art, 2024)
his study delves into the dynamics of viewer engagement and sentiment surrounding the Muara Enggelam documentary video, employing the Cross-Industry Standard Process for Data Mining (CRISP-DM) methodology across six distinct stages. Rooted in the imperative of comprehending audience perceptions and interactions within digital media contexts, particularly in exploring community livelihood and socio-economic dynamics depicted in documentary content, the research traverses through stages encompassing Business Understanding, Data Understanding, Data Preparation, Modeling, Evaluation, and Deployment. Leveraging toxicity analysis utilizing the Perspective API, the study reveals profound insights into the prevalence of negative language within comments, unveiling a low overall toxicity score of 0.04307, with nuanced breakdowns across categories such as Severe Toxicity (0.00476), Identity Attack (0.00978), Insult (0.02652), Profanity (0.03234), and Threat (0.01468). Additionally, Social Network Analysis (SNA) unveils the intricate network structure and interaction patterns among viewers, identifying 1754 nodes and 126 edges in the directed graph, with Modularity at 0.376, Number of Communities at 1653, and an Average Path length of 1.9559594547361063. This analysis highlights the significant role of content creators, exemplified by Kacong Explorer, in shaping discourse and fostering community engagement.